Genomic evolution of cancer metastasis under therapeutic pressure - Qiu‐Luo Liu; Xi Li; Hai‐Ning Chen (MedComm – Oncology, 2022)
Abstract In the era of precision medicine, the selection of cancer treatment relies increasingly on the identification of genomic alterations; however, it is not yet clear how frequently genomic profiling should be performed over the disease course of a patient with metastatic cancer. A large‐scale study investigates the genomic evolution of cancer metastases under therapeutic pressure and finds that the actionable genome has remained relatively stable. The findings support the sufficiency of a single biopsy of cancer metastasis for therapeutic decision‐making.